THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY ON BUSINESS SUSTAINABILITY (GOING CONCERN) (Case Study at PT. TELKOM Surabaya) - Setiawan, Erry; Dewianawati, Dwi (AGUSPATI Research Institute, 2021)
This study aims to examine the effect of corporate social responsibility on corporate business sustainability (Going Concern). The sustainability of the company's business will only be guaranteed if we pay attention to the social and environmental dimensions. In fact, the substance of corporate social responsibility is in the context of strengthening the sustainability of the company's own business by building cooperation between stakeholders which the company facilitates by compiling programs for the surrounding community. This study uses primary data obtained through questionnaires distributed to respondents and also secondary data. The population in this study is the CDC unit (Community Development Center) PT TELKOM Surabaya branch. The number of respondents was 20 respondents who were used in the analysis. The analytical method used is simple regression analysis to analyze the effect of independent variables on dependent variables. Based on the results of the analysis, it was found that Corporate Social Responsibility (Corporate Social Responsibility) Affects the Sustainability of the Company (Going Concern).